Parental behavior and newborn attachment in birds: life history traits and endocrine responses - Mota-Rojas, Daniel; Marcet-Rius, Míriam; Domínguez-Oliva, Adriana; Buenhombre, Jhon; Daza-Cardona, Erika Alexandra; Lezama-García, Karina; Olmos-Hernández, Adriana; Verduzco-Mendoza, Antonio; Bienboire-Frosini, Cécile (Frontiers in Psychology, 2023)
In birds, parental care and attachment period differ widely depending on the species (altricial or precocial), developmental strategies, and life history traits. In most bird species, parental care can be provided by both female and male individuals and includes specific stages such as nesting, laying, and hatching. During said periods, a series of neuroendocrine responses are triggered to motivate parental care and attachment. These behaviors are vital for offspring survival, development, social bonding, intergenerational learning, reproductive success, and ultimately, the overall fitness and evolution of bird populations in a variety of environments. Thus, this review aims to describe and analyze the behavioral and endocrine systems of parental care and newborn attachment in birds during each stage of the post-hatching period.Different life history traits intervene in the survival of the young birds and parental attachment; among them, the development of an adequate nest (size, material, side, purpose), a good physical condition of the parents, the commitment and coordination of males and females during the incubation to provide parental care, the correct release of hormones that are triggered during these This is a provisional file, not the final typeset article processes, parental experience and the incidence of predatory situations. In hatching, other factors can be involved, like the environmental temperature, whether the species are altricial or precocial, and nutritional stress. These numerous and various factors impacting parental care and attachment are important crucial to consider since, in turn, they can influence the development of appropriate social behaviors and endocrine systems in the offspring, hencethus their capability to cope with challenging situations or environments. For this reason, the aim of the present review is to discuss these aspects in different birds according to their level of development at birth (altricial or precocial).